Carbon-coated metal element doped lithium ferrite as well as preparation method and application thereof
By doping metal elements into lithium ferrate materials and using carbon cladding to form a core-shell structure, the problems of irreversible capacity loss and battery gas production in lithium-ion batteries are solved, and the discharge capacity and energy density of lithium-ion batteries are improved , extends battery life.
Patent Information
- Application Number
- CN202411366268.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-13
AI Technical Summary
The solid electrolyte interface film produced by lithium-ion batteries during charging and discharging leads to irreversible capacity loss, reducing energy density and cycle life, and lithium ferrate materials are sensitive to water, and the carbon coating process reduces its discharge capacity, affecting the lithium supplement effect.
The lithium ferrate material is doped with carbon-coated metal elements. By doping elements such as Co, Ni, Cu in the core of lithium ferrate, and using a carbon element coating layer to form a core-shell structure, which increases the discharge capacity and passes through Doping M and N elements reduces gas production in the battery.
It significantly improves the discharge capacity and energy density of lithium-ion batteries, reduces battery gas production, extends the battery cycle life, and simplifies the preparation process.
Smart Images

Figure CN119133653A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon-coated metal element doped lithium ferrite, in particular to a carbon-coated metal element doped lithium ferrite and a preparation method and application thereof, belonging to the field of new energy. Background Art
[0002] During the charge and discharge process of lithium-ion batteries, a large amount of solid electrolyte interface film, namely SEI film, will be produced on the surface of the negative electrode of the battery, which consumes the limited active lithium ions and electrolyte in the battery, resulting in irreversible capacity loss. This process will also reduce the energy density and cycle life of lithium-ion secondary batteries, limiting the application of lithium-ion batteries. The current technology that does not change the electrode preparation process is to add lithium supplement materials to the positive electrode material, which can effectively compensate for the first irreversible capacity loss of lithium batteries caused by the loss of active lithium ions.
[0003] The theoretical charge capacity of lithium ferrite material is as high as 690mAh / g, while the discharge capacity is very small. It can be used as a lithium supplement to supplement the lithium battery during the initial charge and discharge. + However, since lithium ferrite material itself is extremely sensitive to water, it needs to be coated with carbon before it can be used in batteries. The carbon coating process will reduce trivalent iron to divalent iron, which will cause the discharge capacity of lithium ferrite material to decrease and affect the lithium replenishment effect, thus limiting the application of lithium ferrite material in batteries.
[0004] Therefore, developing a lithium ferrite material with higher discharge capacity has become a research direction in this field. Summary of the invention
[0005] The invention provides a carbon-coated metal element doped lithium ferrite, which has the characteristic of high discharge gram capacity.
[0006] The present invention also provides a method for preparing carbon-coated metal element-doped lithium ferrite, which has the characteristic of simple operation.
[0007] The present invention also provides a positive electrode sheet, which has the characteristic of high discharge gram capacity.
[0008] The invention also provides a battery, which has the characteristic of high energy density.
[0009] The present invention provides a carbon-coated metal element-doped lithium ferrite material, wherein the lithium ferrite material has a core-shell structure, the core-shell structure comprises a core and a coating layer, and at least part of the outer surface of the core is provided with the coating layer;
[0010] The core includes L-doped lithium ferrite;
[0011] The L element is selected from at least one of Co, Ni, Cu, Ga, Pb, Sn, Zn, and Rh;
[0012] The coating layer includes a single substance of carbon.
[0013] The carbon-coated metal element doped lithium ferrite material as described above, wherein the core comprises a general chemical formula of Li5Fe x L y M z N 1-x-y-z O4 substances, where 0.9≤x≤1, 0.02≤y≤0.1,
[0014] 0.01≤z≤0.1;
[0015] The M element is selected from at least one of Mn, Cr, V, Ti, Sc, Ca, Zr, Nb, and Mo;
[0016] The N element is selected from at least one of Al, Si, Ti, Ge and Zr.
[0017] The carbon-coated metal element-doped lithium ferrite material as described above, wherein the coating layer is composed of amorphous carbon, and the mass fraction of the coating layer in the lithium ferrite material is 0.1-3wt%; and / or,
[0018] The D50 particle size of the lithium ferrite material is 0.1-20 microns.
[0019] The carbon-coated metal element-doped lithium ferrite material as described above, wherein the charge capacity is greater than or equal to 700 mAh / g; and / or,
[0020] The carbon-coated metal element doped lithium ferrite material has a ferrous ion content of less than or equal to 0.6%.
[0021] The present invention also provides a method for preparing a carbon-coated metal element-doped lithium ferrite material, which comprises the following steps:
[0022] 1) dispersing a mixed system including a lithium source, an iron source, and an L element metal source to obtain a precursor powder;
[0023] 2) sintering the precursor powder to obtain element-doped lithium ferrite;
[0024] 3) performing carbon coating treatment on the element-doped lithium ferrite to obtain the carbon-coated metal element-doped lithium ferrite material;
[0025] The carbon coating treatment is selected from any one of solid phase coating treatment, liquid phase coating treatment, and vapor phase deposition coating treatment.
[0026] The method for preparing the carbon-coated metal element-doped lithium ferrite material as described above, wherein in step 1), the mixed system further includes an M element metal source and an N element metal source.
[0027] The method for preparing the carbon-coated metal element doped lithium ferrite material as described above, wherein the sintering treatment temperature is 650-900°C, the treatment time is 1-20h, and the heating rate is 1-10°C.
[0028] / min.
[0029] The method for preparing the carbon-coated metal element-doped lithium ferrite material as described above, wherein the treatment temperature of the solid phase coating treatment and the liquid phase coating treatment is 400-650° C., and the treatment time is 1-15 hours;
[0030] The treatment temperature of the vapor deposition 1 treatment is 500-650° C., and the treatment time is 10 min-5 h.
[0031] The present invention also provides a positive electrode sheet, which comprises any one of the above-mentioned carbon-coated metal element-doped lithium ferrite.
[0032] The present invention also provides a battery, comprising any one of the above-mentioned carbon-coated metal element-doped lithium ferrite; and / or comprising the above-mentioned positive electrode sheet.
[0033] The carbon-coated metal element-doped lithium ferrite provided by the present invention has the characteristic of high discharge gram capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM photo of carbon-coated metal element-doped lithium ferrite material A1;
[0035] Figure 2 This is the EDS photo of carbon-coated metal element doped lithium ferrite material A1. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0037] A first aspect of the present invention provides a carbon-coated metal element-doped lithium ferrite material, wherein the lithium ferrite material has a core-shell structure, the core-shell structure includes a core and a coating layer, and at least a portion of the outer surface of the core is provided with the coating layer;
[0038] The core includes L-element-doped lithium ferrite;
[0039] The L element is at least one selected from Co, Ni, Cu, Ga, Pb, Sn, Zn, and Rh;
[0040] The coating layer includes simple carbon.
[0041] The carbon-coated metal element doped lithium ferrite material provided by the present invention can be used as a lithium supplement in lithium-ion batteries to compensate for the first irreversible capacity loss of lithium batteries caused by the loss of active lithium ions. Specifically, the carbon-coated metal element doped lithium ferrite material provided by the present invention has a core-shell structure, which includes a core and a coating layer. Among them, the core includes lithium ferrite doped with L element, the coating layer includes a carbon element, and the L element is selected from at least one of Co, Ni, Cu, Ga, Pb, Sn, Zn, and Rh. Lithium ferrite doped with L element is a compound formed by partially replacing the iron position in lithium ferrite with L element. The present invention does not limit the doping amount of L element in L element doped lithium ferrite, and it is sufficient to meet the requirement that the core includes lithium ferrite doped with L element. In one embodiment, the molar ratio of L element to lithium element is 1:10-1:50.
[0042] The present invention does not limit the specific composition of the coating layer, as long as it contains carbon.
[0043] The inventors have found that the carbon-coated metal element doped lithium ferrite material provided by the present invention has the characteristic of high discharge specific capacity. The inventors speculate that the reason may be that in the existing process, during the formation of the coating layer, the carbon element included in the coating layer will reduce the trivalent iron contained in the inner core lithium ferrite to divalent iron, and the divalent iron causes the phase purity of the lithium ferrite to decrease, resulting in a poor lithium supplementation effect. However, the L element is a transition metal element that is variable in valence and easier to reduce than trivalent iron. During the formation of the coating layer, the L element can be reduced before the trivalent iron, and the obtained carbon-coated metal element doped lithium ferrite material has a low content of divalent iron in the inner core, so that the carbon-coated metal element doped lithium ferrite material provided by the present invention has the characteristic of high discharge specific capacity.
[0044] In one embodiment, the core of the carbon-coated metal element-doped lithium ferrite material provided by the present invention comprises a core having a chemical formula of Li5Fe x L y M z N 1-x-y-z O4 substances, where 0.9≤x≤1,
[0045] 0.02≤y≤0.1, 0.02≤z≤0.1;
[0046] The M element is selected from at least one of Mn, Cr, V, Ti, Sc, Ca, Zr, Nb, and Mo;
[0047] The N element is selected from at least one of Al, Si, Ti, Ge, and Zr.
[0048] In this type of lithium ferrite material, the core is lithium ferrite doped with L element, M element and N element at the same time. The inventors found that when this type of lithium ferrite material is used in batteries, it also has the function of reducing battery gas production. The inventors speculate that the reason may be: first, the single-line highly active oxygen generated after the lithium ferrite material is delithiated can oxidize the divalent iron in the positive electrode material lithium iron phosphate or the divalent nickel, divalent manganese, and divalent cobalt in the NCM ternary material after the valence is changed. The above metal ions are precipitated and catalyze the oxidation of the electrolyte, which will cause the battery to produce gas. The doping element M is variable in valence and is easier to oxidize than divalent iron, divalent nickel, divalent manganese, or divalent cobalt. The transition metal element can prevent the single-line high-activity oxygen from oxidizing the divalent iron in the positive electrode material lithium iron phosphate or the divalent nickel, divalent manganese and divalent cobalt in the NCM ternary material after valence change, thereby reducing the gas production of the battery; secondly, N is a transition metal element whose binding energy with oxygen is greater than that of the Fe-O bond. The binding energy between N and oxygen is relatively high, and the NO bond is not easy to break. When N partially replaces iron, it can reduce the single-line high-activity oxygen generated by the breakage of the Fe-O bond and the precipitated Fe+ catalyzing the oxidation of the electrolyte, leading to gas production in the battery.
[0049] Therefore, the carbon-coated metal element-doped lithium ferrite material obtained by simultaneously adding L, M, and N elements to lithium ferrite not only has a good lithium replenishment effect, but also has the function of reducing battery gas production.
[0050] Furthermore, in one embodiment, the coating layer is composed of amorphous carbon, and the mass fraction of the coating layer in the lithium ferrite material is 0.1-3wt%. Since carbon can reduce the powder impedance of the material, the lithium ferrite material with a suitable coating layer mass fraction is more likely to exert its capacity advantage.
[0051] In one embodiment, the D50 particle size of the core in the carbon-coated metal element-doped lithium ferrite material provided by the present invention is 5-15 microns, more preferably 5-15 microns, and the thickness of the coating layer is 50-100 nanometers. Since reducing the particle size can reduce the Li ion transmission path principle, the lithium ferrite material with the above characteristics has the advantage of being easier to exert capacity and more prominent.
[0052] Furthermore, in one embodiment, the discharge capacity of the carbon-coated metal element-doped lithium ferrite material provided by the present invention is not less than 700 mAh / g. The lithium ferrite material has the characteristic of high discharge capacity.
[0053] Furthermore, in one embodiment, the carbon-coated metal element doped lithium ferrite material provided by the present invention has a ferrous ion content of less than or equal to 0.6%. Due to the lower divalent iron content, the carbon-coated metal element doped lithium ferrite material with the above characteristics has a stronger lithium supplementation effect.
[0054] The second aspect of the present invention provides a method for preparing a carbon-coated metal element doped lithium ferrite material, which can be used to prepare any carbon-coated metal element doped lithium ferrite material provided in the first aspect of the present invention. The method comprises the following steps:
[0055] 1) dispersing a mixed system including a lithium source, an iron source, and an L element metal source to obtain a precursor powder;
[0056] 2) Sintering the precursor powder to obtain element-doped lithium ferrite;
[0057] 3) The element-doped lithium ferrite is subjected to carbon coating treatment to obtain a carbon-coated metal element-doped lithium ferrite material.
[0058] The present invention does not limit the specific composition of the lithium source, the iron source, and the L element metal source, as long as they meet the requirements of containing lithium element, iron element, and L element respectively. In one embodiment, the lithium source is selected from at least one of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium oxide, and lithium nitrate, the iron source is selected from at least one of 100-500nm iron oxide, iron nitrate nonahydrate, iron hydroxide, and iron oxyhydroxide, and the L element metal source is selected from at least one of the oxide, carbide, sulfide, carbonate, hydroxide, oxalate, citrate, and acetate of the L element.
[0059] Furthermore, the present invention does not limit the ratio of the lithium source, the iron source, and the L element metal source, and the commonly used ratio in the art can be used as long as the requirement of producing a carbon-coated metal element-doped lithium ferrite material is met.
[0060] The function of the dispersion treatment is to mix the lithium source, the iron source, and the L element metal source. The present invention does not limit the specific treatment method of the dispersion treatment. In one embodiment, the dispersion treatment includes using a ball mill for ball milling, the ball milling speed is 1000-2000 rpm, and the time is 0.5-5 hours; or a mixer can be used for stirring, the mixer speed is 500-20000 rpm, and the time is 10 minutes to 2 hours. When the treatment system presents a state where the particle size D50 is less than 10 microns, the dispersion treatment is stopped.
[0061] The role of the sintering treatment is to make Li ions migrate to the iron oxide tetrahedron to generate lithium ferrite material. The present invention does not limit the specific treatment conditions of the sintering treatment, and the common sintering conditions in the field can be used, as long as the requirements of obtaining carbon-coated metal element-doped lithium ferrite material are met. In one embodiment, the treatment temperature of the sintering treatment is 500-1000°C, and the treatment time (ie, constant temperature time) is 1-20h. The precursor powder is sintered to obtain element-doped lithium ferrite, which is the core of the carbon-coated metal element-doped lithium ferrite material.
[0062] The carbon coating process is used to form a coating layer on the outer surface of the inner core, thereby obtaining the carbon-coated metal element doped lithium ferrite material provided by the first aspect of the present invention. The carbon coating process can improve the air stability (avoiding the reaction with water in the air to form a LiFeO2 impurity phase) and increase the electronic conductivity, making the obtained carbon-coated metal element doped lithium ferrite material have a higher discharge specific capacity.
[0063] The carbon coating treatment is selected from any one of solid-phase coating treatment, liquid-phase coating treatment, and vapor-phase deposition coating treatment, wherein the solid-phase carbon coating treatment is to mix the element-doped lithium ferrite with the carbon source and then roast it, and the carbon source is converted into a carbon single substance and coated on the surface of the element-doped lithium ferrite, thereby obtaining a carbon-coated metal element-doped lithium ferrite material; the liquid-phase carbon coating treatment is to dissolve the carbon source in a solvent, mix the obtained mixed system with the element-doped lithium ferrite, and then dry it, so that the solvent is separated from the mixed system and the carbon source is combined with the element-doped lithium ferrite, and finally the carbon source is converted into a carbon single substance and coated on the element-doped lithium ferrite by sintering treatment, so as to obtain a carbon-coated metal element-doped lithium ferrite material. The vapor-phase carbon coating treatment is to coat the carbon single substance generated by the decomposition of the gaseous carbon source on the surface of the element-doped lithium ferrite, so as to obtain a carbon-coated metal element-doped lithium ferrite material. The present invention does not limit the specific conditions of the carbon coating treatment, and it is sufficient to meet the requirements of obtaining a carbon-coated metal element-doped lithium ferrite material.
[0064] Furthermore, in one embodiment, the carbon source for solid phase coating treatment and liquid phase coating treatment is selected from at least one of glucose, sucrose, polyethylene glycol, polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, and phenolic resin; the carbon source for vapor deposition coating treatment is selected from at least one of methane, acetylene, ethylene, propylene, benzene, and carbon monoxide; and the solvent for liquid phase coating treatment can use common organic solvents in the art, such as at least one of nmp, tetrahydrofuran, and dimethyl sulfoxide.
[0065] The method for preparing the carbon-coated metal element-doped lithium ferrite material provided by the present invention has the characteristic of relatively simple operation.
[0066] In one embodiment, the mixed system also includes an M element metal source and an N element metal source. That is, in step 1), a mixed system including a lithium source, an iron source, an L element metal source, an M element metal source, and an N element metal source is dispersed to obtain a precursor powder. Among them, the M element metal source is selected from at least one of the oxides, carbides, sulfides, carbonates, hydroxides, oxalates, citrates, and acetates of the M element, and the N element metal source is selected from at least one of the oxides, carbides, sulfides, carbonates, hydroxides, oxalates, citrates, and acetates of the N element. The present invention does not limit the molar ratio of the lithium source, the iron source, the L element metal source, the M element metal source, and the N element metal source, as long as the carbon-coated metal element-doped lithium ferrite material provided in the first aspect of the present invention can be obtained. In one embodiment, the molar ratio of lithium element, iron element, L element, M element, and N element in the lithium source, iron source, L element metal source, M element metal source, and N element metal source is (5-5.5): (0.9-1): (0.02-0.1): (0.01-0.1): (0.01-0.1). The carbon-coated metal element-doped lithium ferrite material prepared by the preparation method that meets the above molar ratio has a higher discharge gram capacity and a more prominent technical effect.
[0067] In one embodiment, the sintering treatment temperature is 650-900°C, the treatment time is 1-20h, and the heating rate is 1-10°C / min. The carbon-coated metal element doped lithium ferrite material prepared under the above treatment conditions has a more prominent technical effect of higher discharge capacity.
[0068] Further, in one embodiment, the treatment temperature of the solid phase coating treatment and the liquid phase coating treatment is 400-650° C., and the treatment time is 1-15 h;
[0069] The treatment temperature of the vapor deposition treatment is 500-650°C, and the treatment time is 10min-5h. The technical effect of the carbon-coated metal element-doped lithium ferrite material with higher discharge capacity obtained under the above treatment conditions is more prominent.
[0070] A third aspect of the present invention provides a positive electrode sheet, which comprises any one of the above-mentioned carbon-coated metal element-doped lithium ferrite materials.
[0071] The positive electrode sheet of the present invention specifically includes a positive electrode current collector and a positive electrode active layer formed of a positive electrode active material and arranged on the surface of the positive electrode current collector.
[0072] When preparing the positive electrode sheet, for example, the carbon-coated metal element-doped lithium ferrite material provided by the present invention, the positive electrode active material and the binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the positive electrode active layer includes 70-99wt% of positive electrode active material, 0.5-15wt% of conductive agent, and 0.5-15wt% of binder according to the mass percentage, and further includes 80-98wt% of positive electrode active material, 1-10wt% of conductive agent, and 1-10wt% of binder.
[0073] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.
[0074] Since the carbon-coated metal element-doped lithium ferrite material provided by the present invention has the characteristic of high discharge gram capacity, the positive electrode sheet provided by the present invention has strong lithium replenishment performance.
[0075] A fourth aspect of the present invention provides a battery, which comprises any of the carbon-coated metal element-doped lithium ferrite materials or the positive electrode sheet, and has the characteristic of high energy density.
[0076] It is conceivable that the battery provided by the present invention includes, in addition to the above-mentioned positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.
[0077] The present invention does not strictly limit the positive electrode active material in the positive electrode sheet, and can be a positive electrode active material commonly used in lithium-ion batteries, such as at least one composite oxide of lithium and metals of cobalt, manganese, nickel and combinations thereof. Specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium manganate, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate (LFP), lithium nickel manganate, lithium-rich manganese-based material, etc.
[0078] The present invention does not strictly limit the selection of the electrolyte, and may include one or more of the solvents commonly used in lithium-ion battery electrolytes, and electrolyte lithium salts commonly used in lithium-ion electrolytes, for example: the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the lithium salt may be, for example, one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0079] The present invention does not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in lithium-ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, or a diaphragm with a ceramic coating.
[0080] When preparing lithium-ion batteries, the positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery, and the battery is placed, formed and sealed for the second time to complete the preparation of the lithium-ion battery.
[0081] The carbon-coated metal element-doped lithium ferrite material provided by the present invention and its preparation method and application are further described below through examples.
[0082] Example 1
[0083] 1) lithium hydroxide monohydrate, nano iron oxide, aluminum oxide, cobalt tetraoxide, and molybdenum trioxide are weighed according to the molar ratio of lithium, iron, aluminum, cobalt, and molybdenum elements of 5.1:0.92:0.05:0.02:0.01, and put into a mixer for dispersion treatment. The mixer speed is 800 rpm, and the treatment time is 30 minutes. When D50 in the treatment system is less than 10 microns, a precursor powder is obtained;
[0084] 2) placing the precursor powder into an alumina crucible, and sintering the precursor powder in a nitrogen atmosphere in a tubular furnace, wherein the heating rate is 3°C / min, the treatment temperature is 500°C, and the treatment time (i.e., constant temperature time) is 5h, and then heating the precursor powder to 830°C at a heating rate of 3°C / min, and the treatment time (i.e., constant temperature time) is 10h. After being crushed and sieved by a pulverizer, an element-doped lithium ferrite material is obtained;
[0085] 3) The element-doped lithium ferrite material was solid-phase mixed with glucose and polyethylene glycol in a mass ratio of 95:5:1, and treated at 500°C for 10 hours in a nitrogen atmosphere. After sieving, the carbon-coated metal element-doped lithium ferrite material A1 was obtained. The carbon-coated metal element-doped lithium ferrite material A1 was subjected to SEM testing, and the obtained image is as follows: Figure 1 As shown; the material was subjected to EDS testing of carbon elements, and the resulting image is as follows Figure 2 As shown. Figure 2 It can be seen that the surface of the material is evenly covered with carbon.
[0086] The chemical formula of the carbon-coated metal element doped lithium ferrite material A1 core is
[0087] Li5Fe 0.92 Al 0.05 Co 0.02 Mo 0.01 O4, the D50 particle size of the material was measured to be 8 μm using a Malvern 3000 laser particle size analyzer, and the mass fraction of the coating layer was measured to be 1.8% using a carbon-sulfur analyzer (Sichuan Sai Ensi HCS-801 high-frequency infrared carbon-sulfur analyzer).
[0088] Example 2
[0089] This embodiment is basically the same as Embodiment 1, except that, in step 1), alumina is replaced by titanium dioxide containing the same molar amount of metal elements (meaning that the aluminum element contained in alumina is equal to the titanium element contained in titanium dioxide in molar amount, and the same meaning is hereinafter applied), cobalt tetroxide is replaced by nickel oxide containing the same molar amount of metal elements, and molybdenum trioxide is replaced by niobium oxide containing the same molar amount of metal elements; in step 3), the carbon source for carbon coating is replaced by sucrose and polyvinyl pyrrolidone from glucose and polyethylene glycol, and the ratio of sucrose to polyvinyl pyrrolidone is 1:1, so that the mass fraction of the coating layer in the prepared sample is the same as that in Embodiment 1.
[0090] A carbon-coated metal element-doped lithium ferrite material A2 is obtained.
[0091] The chemical formula of the carbon-coated metal element doped lithium ferrite material A2 core is Li5Fe 0.92 Ti 0.05 Ni 0.02 Nb 0.01 O4, D50 particle size is 6 microns, and the mass fraction of the coating layer is 1.8wt%.
[0092] Example 3
[0093] This embodiment is basically the same as embodiment 1, except that, in step 3), vapor deposition coating is used for carbon coating treatment, methane is used as a carbon source, and the temperature is kept constant at 600°C for 1 hour. Specifically, the vapor deposition coating includes heating the sample to 600 degrees Celsius, introducing acetylene gas for constant temperature reaction, and then naturally cooling the sample, and controlling the reaction time so that the mass fraction of the coating layer in the obtained sample is 2.0wt%.
[0094] The carbon-coated metal element-doped lithium ferrite material A3 is obtained.
[0095] The chemical formula of the carbon-coated metal-doped lithium ferrite material A3 core is Li5Fe 0.92 Al 0.05 Co 0.02 Mo 0.01 O4, D50 particle size is 10 microns, and the mass fraction of the coating layer is 2.0wt%.
[0096] Example 4
[0097] This embodiment is basically the same as Embodiment 3, except that:
[0098] Aluminum oxide is replaced by zirconium oxide of the same molar amount, cobalt oxide is replaced by zinc oxide containing the same molar amount of a metal element, and molybdenum trioxide is replaced by manganese monoxide containing the same molar amount of a metal element.
[0099] The carbon-coated metal element-doped lithium ferrite material A4 is obtained.
[0100] The chemical formula of the carbon-coated metal-doped lithium ferrite material A4 core is Li5Fe 0.92 Zr 0.05 Zn 0.02 Mn 0.01 O4, D50 particle size is 7 microns, and the mass fraction of the coating layer is 1.8wt%.
[0101] Example 5
[0102] This embodiment is basically the same as embodiment 1, except that in step 3), liquid phase coating is used for carbon coating treatment, the carbon sources are polyvinylidene fluoride and polyethylene glycol, and the solvent is NMP.
[0103] Specifically, the liquid phase coating includes: dissolving polyvinylidene fluoride and polyethylene glycol in NMP solvent and then mixing with element-doped lithium ferrite material, drying the mixed system and then sintering, and controlling the mass of polyvinylidene fluoride and polyethylene glycol so that the mass fraction of the coating layer in the prepared sample is 1.3wt%.
[0104] The carbon-coated metal element-doped lithium ferrite material A5 was obtained.
[0105] The chemical formula of the carbon-coated metal-doped lithium ferrite material A5 core is Li5Fe0.92 Al 0.05 Co 0.02 Mo 0.01 O4, D50 particle size is 7 microns, and the mass fraction of the coating layer is 1.3wt%.
[0106] Example 6
[0107] This embodiment is basically the same as the embodiment 1, except that, in step 1), no aluminum oxide and molybdenum trioxide are added, and only lithium hydroxide monohydrate, nano-iron oxide, and cobalt tetroxide are weighed and mixed according to the molar ratio of lithium, iron, and cobalt elements of 5.1:0.92:0.08.
[0108] The carbon-coated metal element-doped lithium ferrite material A6 was obtained.
[0109] The chemical formula of the carbon-coated metal-doped lithium ferrite material A6 core is Li5Fe 0.92 Co 0.08 O4, D50 particle size is 8 microns, and the mass fraction of the coating layer is 1.8wt%.
[0110] Comparative Example 1
[0111] This comparative example is basically the same as Example 1, except that in step 1), no aluminum oxide, cobalt tetroxide, or molybdenum trioxide is added, and only lithium hydroxide monohydrate and nano-iron oxide are weighed and mixed in a molar ratio of 5.1:1.
[0112] The carbon-coated lithium ferrite material B1 was obtained.
[0113] Comparative Example 2
[0114] This comparative example is basically the same as Example 1, except that, in step 1), cobaltous oxide is not added, and only lithium hydroxide monohydrate, nano-iron oxide, aluminum oxide, and molybdenum trioxide are weighed and mixed according to the molar ratio of lithium, iron, aluminum, and molybdenum elements of 5.1:0.94:0.05:0.01.
[0115] The carbon-coated metal element-doped lithium ferrite material B2 is obtained.
[0116] Test example
[0117] 1. Test of divalent iron ion content
[0118] The lithium ferrite materials prepared in each embodiment and comparative example were tested for the content of divalent iron ions, and the test was carried out in accordance with the standard GB / T34176-2017 "Chemical Analysis Method for Determination of Divalent and Trivalent Iron Ions in Refractory Materials by Spectrophotometry of Phenomenaline". The test results are shown in Table 1.
[0119] Table 1 Test data of divalent iron ion content
[0120] serial number <![CDATA[Fe 2+ Content (%)]]> Example 1 0.17 Example 2 0.19 Example 3 0.09 Example 4 0.08 Example 5 0.16 Example 6 0.58 Comparative Example 1 20.41 Comparative Example 2 20.26
[0121] It can be seen from Table 1 that the sample doped with L element has a lower divalent iron ion content than the sample not doped with L element.
[0122] 2. Gas production test
[0123] The carbon-coated metal element-doped lithium ferrite prepared in each embodiment and comparative example was compounded with lithium iron phosphate as the positive electrode material to prepare a soft-pack battery. The amount of lithium ferrite added was 2% of the positive electrode active material. After weighing according to the ratio of positive electrode active material: SP: PVDF = 96:2:2, it was added to a double planetary mixer, and an appropriate amount of NMP was added to mix and fully make a slurry, which was coated, dried, and rolled to obtain a positive electrode sheet; the negative electrode was artificial graphite, which was weighed according to the ratio of negative electrode active material: CMC: SBR: SP = 94:1:2:3, and then added to a double planetary mixer, and an appropriate amount of deionized water was added to mix and fully make a slurry, which was coated, dried, and rolled to obtain a negative electrode sheet, and then the positive electrode sheet and the negative electrode sheet were assembled into a lithium-ion secondary battery, and the formation and capacity separation were performed respectively, and then the gas production test was performed. The test temperature was 70°C, the time was 28 days, and the formation cut-off voltage was 4.3V. The results are shown in Table 2.
[0124] Table 2 Gas production test data
[0125] serial number Gas production rate (%) Example 1 16.8 Example 2 16.1 Example 3 14.6 Example 4 15.8 Example 5 16.0 Example 6 37.6 Comparative Example 1 38.3 Comparative Example 2 17.5
[0126] As can be seen from Table 2, since the samples prepared in Example 6 and Comparative Example 1 do not include both the M element and the N element, the gas generation rate of the lithium ion secondary battery prepared is higher than that of other samples.
[0127] As can be seen from the above, the technical solution of the present invention can effectively improve the problem of trivalent iron being reduced to divalent iron caused by carbon coating, which is mainly due to the fact that the doped elements are reduced before trivalent iron; further, the present invention can also effectively improve the high-temperature storage gas production performance of the battery, which is mainly due to the fact that the doped elements can prevent highly active oxygen from oxidizing the positive electrode material, causing metal ions to precipitate and then catalyze the oxidation of the electrolyte, and can prevent and reduce the breakage of Fe-O bonds to produce single-line highly active oxygen and Fe + The catalytic electrolyte precipitation causes the battery to produce gas.
[0128] 3. Discharge capacity test
[0129] The carbon-coated metal element-doped lithium ferrite positive electrode materials of the embodiments and comparative examples are respectively made into positive electrode sheets, and then assembled with negative electrode sheets, electrolytes and separators according to the following method to obtain button batteries. The method includes:
[0130] Each positive electrode active material was mixed with conductive carbon black (SP) and PVDF in a weight ratio of 80%:10%:10% to obtain a positive electrode slurry by dispersion. The slurry was coated on an aluminum foil current collector and rolled to obtain a surface density of 10 g / cm 3 The positive electrode sheet is then punched out into a small disc with a diameter of 12 mm using a film mold. After drying and weighing, a button battery is assembled in a glove box under an Ar protective atmosphere using a 2025 button battery shell, a Li metal disc as the negative electrode, and the electrolyte Xinzhoubang LBC3021C48.
[0131] Using a blue battery charge and discharge tester, the battery was charged to 4.25V at 0.1C constant current at 25°C, then charged at constant voltage until the current dropped to 0.05C. After standing for 5 minutes, the battery was discharged to 2.5V at 0.1C constant current, and the charged gram capacity displayed by the tester was recorded. The results are shown in Table 3.
[0132] Table 3 Capacity test data
[0133]
[0134] It can be seen from Table 3 that the carbon-coated metal element-doped lithium ferrite positive electrode materials prepared in Comparative Examples 1 and 2 have lower charging capacity than those in Examples 1-6. The reason may be that the materials prepared in Comparative Examples 1 and 2 do not include the L element, and the presence of divalent iron during the preparation process causes the charging capacity to decrease.
[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carbon-coated metal element doped lithium ferrite material, It is characterized in that The lithium ferrite material has a core-shell structure, the core-shell structure includes a core and a coating layer, and the coating layer is provided on at least part of the outer surface of the core; The core includes L-doped lithium ferrite; The L element is selected from at least one of Co, Ni, Cu, Ga, Pb, Sn, Zn, and Rh; The coating layer includes a single substance of carbon.
2. The carbon-coated metal element-doped lithium ferrite material according to claim 1, It is characterized in that The core comprises a chemical formula of Li 5 Fe x L y M z N 1-x-y-z O 4 A substance, where 0.9≤x≤1, 0.02≤y≤0.1, 0.01≤z≤0.1; The M element is selected from at least one of Mn, Cr, V, Ti, Sc, Ca, Zr, Nb, and Mo; The N element is selected from at least one of Al, Si, Ti, Ge and Zr.
3. The carbon-coated metal element-doped lithium ferrite material according to claim 1 or 2, It is characterized in that The coating layer is composed of amorphous carbon, and the mass fraction of the coating layer in the lithium ferrite material is 0.1-3wt%; and / or, The D50 particle size of the lithium ferrite material is 0.1-20 microns.
4. The carbon-coated metal element-doped lithium ferrite material according to any one of claims 1 to 3, It is characterized in that The charge capacity is greater than or equal to 700 mAh / g; and / or, The carbon-coated metal element doped lithium ferrite material has a ferrous ion content of less than or equal to 0.6%.
5. A method for preparing the carbon-coated metal element-doped lithium ferrite material according to any one of claims 1 to 4, It is characterized in that The steps include: 1) dispersing a mixed system including a lithium source, an iron source, and an L element metal source to obtain a precursor powder; 2) sintering the precursor powder to obtain element-doped lithium ferrite; 3) performing carbon coating treatment on the element-doped lithium ferrite to obtain the carbon-coated metal element-doped lithium ferrite material; The carbon coating treatment is selected from any one of solid phase coating treatment, liquid phase coating treatment, and vapor phase deposition coating treatment.
6. The method according to claim 5, It is characterized in that In step 1), the mixed system further includes an M element metal source and an N element metal source.
7. The method according to claim 5 or 6, It is characterized in that The sintering treatment has a treatment temperature of 650-900° C., a treatment time of 1-20 hours, and a heating rate of 1-10° C. / min.
8. The method according to any one of claims 5 to 7, It is characterized in that The treatment temperature of the solid phase coating treatment and the liquid phase coating treatment is 400-650°C, and the treatment time is 1-15h; The processing temperature of the vapor deposition process is 500-650° C., and the processing time is 10 min-5 h.
9. A positive electrode sheet, It is characterized in that The carbon-coated metal element-doped lithium ferrite material comprises the carbon-coated metal element-doped lithium ferrite material according to any one of claims 1 to 4.
10. A battery, It is characterized in that The carbon-coated metal element-doped lithium ferrite material according to any one of claims 1 to 4; and / or Including the positive electrode sheet as described in claim 9.
Citation Information
Cited By
Low-gas-production iron-based composite lithium supplementing material and preparation method thereof, lithium ion battery and electric equipment
CN121215737A
Method for detecting content of ferrous iron impurities in lithium supplementing material and application of method
CN121522081A
